The application of artificial gravity in medicine and space - Isasi, Eugenia; Isasi, Maria E.; van Loon, Jack J. W. A. (Frontiers in Physiology, 2022)
Gravity plays a crucial role in physiology. The lack of gravity, like in long duration spaceflight missions, cause pathologies in e.g., the musculoskeletal system, cardiovascular deconditioning, immune system deprivation or brain abnormalities, to just mention a few. The application of artificial gravity through short-arm human centrifugation (SAHC) has been studied as a possible countermeasure to treat spaceflight deconditioning. However, hypergravity protocols applied by using SAHC have also been used to treat different, ground-based pathologies. Such gravitational therapies have been applied in Uruguay for more than four decades now. The aim of this review is to summarize the most important findings about the effects of gravitational therapy in different, mainly vascular based, pathologies according to the experience in the Gravitational Therapy Center and to discuss the current research in the field of hypergravity applications in medicine but also as multisystem countermeasure for near weightlessness pathologies. New insight is needed on the use of hypergravity in medicine and space research and application.